2003
DOI: 10.1007/s00466-003-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Radial basis function method for 1-D and 2-D groundwater contaminant transport modeling

Abstract: In this paper we develop a meshless method for modeling groundwater contaminant transport. The algorithm uses collocation method with radial basis functions. Numerical results are presented for several cases: pure diffusion; advection and dispersion for continuous source; advection and dispersion for instantaneous source; advection and dispersion for patch-source. The results show that the method is very simple and accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…From Fig. 4, it is observed that both the RPIM and analytical results, as well results from Li et al (2003) are in agreement with one another.…”
Section: Numerical Examplessupporting
confidence: 91%
See 2 more Smart Citations
“…From Fig. 4, it is observed that both the RPIM and analytical results, as well results from Li et al (2003) are in agreement with one another.…”
Section: Numerical Examplessupporting
confidence: 91%
“…The RPIM is applied to the problem considered by Li et al (2003). The model is applied to a soil column of horizontal length of 100 units with initial condition C (x, 0) = 0 and boundary conditions C (x, t) = 1.0 units at x = 0 and oC x;t ð Þ ox ¼ 0 at x = 100 units.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EFGM is applied to the problem considered by Li et al [19]. The model is applied to a soil column of horizontal length of 100 units with initial condition C(x, 0) = 0 and boundary conditions 672 R. PRAVEEN KUMAR AND G. R. DODAGOUDAR …”
Section: Example 2: Validation With Published Data: Advection-dispersionmentioning
confidence: 99%
“…Among all the meshfree methods, element-free Galerkin method (EFGM) has been successfully used for solving numerous boundary value problems related to various fields of study [11][12][13][14][15][16]. A limited amount of research is undertaken regarding the potential usage of the meshfree methods for modelling contaminant transport processes in the saturated porous media and in the area of landfill engineering [17][18][19].…”
Section: Introductionmentioning
confidence: 99%